Unsur-Unsur Komunikasi Pelayanan Publik (Sebuah Tinjauan Literatur) - Tatang Wahyono; Rafinita Aditia (Universitas Dehasen Bengkulu, 2022)
In service activities, service quality depends on the elements of public service communication. The element of communication plays a very important role in improving the quality of public services. Therefore, the communication factor needs to be a serious concern for public service organizations. Failure to establish public service communication can interfere with public service information and affect the quality of public services. The poor quality of public services has an impact on the low level of public or public trust in public service providers. Writing this article aims to review and synthesize the available literature related to the elements in public service communication so that it can contribute to an understanding of the elements of service communication in the public sector. The results showed that the elements of public service communication consisted of communicators, messages, media, communicants, and effects in the communication process. The five elements influence each other, relate to each other to form a single unit. If the five elements of public service are not fulfilled, it will have an impact on the low level of public or public trust in public service providers.